What Are Education Students’ Perceptions of the Role of Technology in Social Studies Pedagogy? - Gibson, Susan; Moline, Teddy; Dyck, Brenda (Alberta Journal of Educational Research, 2011)
Preservice teachers need both awareness of and skill with the latest digital technologies in order to use these tools effectively in their teaching. Historically in our university, this preparation has been reserved for a stand-alone information technology course focused on learning how to use various computer-based programs. However, more direct experience in subject-specific pedagogy courses is necessary to develop a deeper understanding about how a technology-rich environment can help to develop subject-specific knowledge. The study reported here examined the influences of two technology-infused social studies pedagogy courses on students’ perceptions about why, when, and how most effectively to infuse technology in their teaching of social studies and their feelings of preparedness to use those technologies. Les stagiaires doivent être au courant des technologies numériques et ils doivent savoir s'en servir de sorte à les intégrer efficacement à leur enseignement. Dans notre université, cette préparation a toujours été offerte dans le contexte d'un cours autonome portant sur la technologie de l'information et l'emploi de divers programmes informatiques. Toutefois, il faut avoir plus d'expériences directes dans des cours de pédagogie disciplinaires afin de pouvoir mieux tirer profit d'un milieu riche sur le plan informatique dans le développement de connaissances spécifiques aux disciplines. Cet article décrit une étude portant sur deux cours de pédagogie hautement informatisés et ayant trait aux études sociales. On a examiné, d'une part, les perceptions des étudiants quant à l'intégration efficace de la technologie dans leur enseignement des études sociales (pourquoi, quand et comment) et, d'autre part, la mesure dans laquelle ils se sentaient prêts à employer ces technologies.